2008
DOI: 10.1038/nn.2173
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of fMRI and neural signals in V1 during perceptual suppression in the awake monkey

Abstract: The role of primary visual cortex (V1) in determining the contents of perception is controversial. Human functional imaging (fMRI) studies of perceptual suppression have revealed a robust drop in V1 activity when a stimulus is subjectively invisible. In contrast, monkey single unit recordings have failed to demonstrate such perception locked changes in V1. To investigate the basis of this discrepancy, we measured both the blood oxygenation level-dependent (BOLD) response and several electrophysiological signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
256
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 280 publications
(276 citation statements)
references
References 39 publications
16
256
4
Order By: Relevance
“…This high frequency spectral power change has been shown to correlate directly with firing rate [Manning et al, 2009;Miller et al, 2009a;Whittingstall and Logothetis, 2009], and has been demonstrated to reflect broadspectral change across all frequencies Miller et al, 2009b]. Previous studies examined the relationship between spectral power change and BOLD change within a specific region [Logothetis et al, 2001;Maier et al, 2008;Mukamel et al, 2005;Niessing et al, 2005]. We extend this relationship found at the neuronal population volumes sampled by microelectrodes [<500 lm (Katzner et al, 2009)] to a widespread network of movement-related regions on the cortical surface.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This high frequency spectral power change has been shown to correlate directly with firing rate [Manning et al, 2009;Miller et al, 2009a;Whittingstall and Logothetis, 2009], and has been demonstrated to reflect broadspectral change across all frequencies Miller et al, 2009b]. Previous studies examined the relationship between spectral power change and BOLD change within a specific region [Logothetis et al, 2001;Maier et al, 2008;Mukamel et al, 2005;Niessing et al, 2005]. We extend this relationship found at the neuronal population volumes sampled by microelectrodes [<500 lm (Katzner et al, 2009)] to a widespread network of movement-related regions on the cortical surface.…”
Section: Discussionmentioning
confidence: 64%
“…Since ECoG is sampled relatively sparse with 1 cm inter electrode spacing, it should be considered that the part of BOLD signal change explained by low frequency changes is actually due to missed high frequency activity. On motor cortex however, responses for individual fingers can be captured with 1 cm spaced ECoG electrodes [Miller et al, 2009b] and previous studies sampling at smaller scales in 1 area of cortex have also reported low frequency correlation with BOLD when no spiking or high frequency LFP power change could be found [Maier et al, 2008]. This possibility should however be further explored in other studies using higher resolution spatial sampling.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our findings demonstrate that neurovascular coupling is itself dynamic and subject to behavioral state (see also ref. 53). This adds to recent work showing that correlation patterns in both fMRI (22,26) and neural (42,54) signals vary as a function of behavioral state.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are now becoming feasible for non-human primates (Conway et al, 2007;Goense et al, 2008;Kayser et al, 2007;Maier et al, 2008;Op de Beeck et al, 2008), but still remain a challenge for application in alert and behaving rodents, the most commonly used experimental animals. One reason for that is that the majority of behavioral paradigms developed for rodents often require active locomotion as a behavioral expression of a particular cognitive function.…”
mentioning
confidence: 99%